2006
DOI: 10.1016/j.trstmh.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Natural transmission of Plasmodium knowlesi to humans by Anopheles latens in Sarawak, Malaysia

Abstract: a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e l s e v i e r h e a l t h . c o m / j o u r n a l s / t r s t SHORT COMMUNICATION Natural transmission of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
130
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 9 publications
2
130
0
3
Order By: Relevance
“…En condiciones experimentales se han inducido infecciones con P. knowlesi en Callithrix jacchus (30) (26,34). Ninguna de éstas está documentada en Colombia (35).…”
Section: Huéspedes Y Vectores Naturalesunclassified
See 1 more Smart Citation
“…En condiciones experimentales se han inducido infecciones con P. knowlesi en Callithrix jacchus (30) (26,34). Ninguna de éstas está documentada en Colombia (35).…”
Section: Huéspedes Y Vectores Naturalesunclassified
“…La búsqueda de huéspedes y vectores para determinar el potencial zoonótico de esta infección, se inició en Malasia (34,36). Anopheles hackeri se identificó como el vector más importante de P. knowlesi (37), A. balabacencis introlatus, como el vector de P. cynomolgi (38), y A. leucosphyrus como el de P. inui (39), plasmodios causantes de malaria en simios.…”
Section: Huéspedes Y Vectores Naturalesunclassified
“…These investigators used Anopheles balabacensis, a member of the Leucosphyrus complex placed under the Leucosphyrus Group (Sallum et al 2005). The proof that P. knowlesi in humans is a case of malaria zoonoses came from studies by Vythillingam et al (2006Vythillingam et al ( , 2008. In Sarawak Lee et al (2011) Malaysia, specimens of An.…”
Section: Clinical Symptoms Of P Knowlesi Infections and Treatmentmentioning
confidence: 99%
“…cracens (a member of the Dirus Complex) and An. latens (a member of the Leucosphyrus Complex) were incriminated as vectors of P. knowlesi in humans in Malaysian Borneo and Peninsular Malaysia respectively (Vythillingam et al 2006(Vythillingam et al , 2008). An.…”
Section: Clinical Symptoms Of P Knowlesi Infections and Treatmentmentioning
confidence: 99%
“…To our knowledge this is the first report of the detection of P. knowlesi together with P. falciparum and P. vivax in an individual mosquito from a population that acts as the principal human malaria vector in a given area. Studies on P. knowlesi transmission in Malaysia (Vythilingam et al, 2006(Vythilingam et al, , 2008 identified a vector species that, although belonging to the Anopheles leucosphyrus group, is at present not implicated in the transmission of human malaria parasites. Our report shows that P.…”
mentioning
confidence: 99%